Pendampingan Penyusunan Artikel Ilmiah Bagi Guru MGMP PPKn Kota Surabaya Berbasis Kurikulum Merdeka - Akhmad Qomaru Zaman; Irnawati Irnawati; I Wayan Arsana; Oksiana Jatiningsih; Nurul Ainni; Risma Widia Ramadhanti (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Teachers often encounter many obstacles when writing scientific articles. One of them is limited knowledge about how to write scientific papers and how to use reference applications. Another obstacle is the lack of motivation, especially to produce quality scientific papers. Limited access to good literature also poses obstacles in the writing process. In fact, legally, teachers are regulated to be able to develop their competence and professionalism, one of which is by writing. This activity is a solution to these problems with a participatory approach aimed at overcoming a problem encountered by teachers. The results of the activity are shown by the enthusiasm of teachers in learning scientific writing which will later be given a container in the form of a journal for publication of their writings.